Cabaran PdPR menggunakan aplikasi buku teks digital Pendidikan Islam KSSR - Mustafa, Abdul Syahid; Azarai, Muaz; Mustafa, Muhammad ‘Izzat; Salleh, Zakiah; Mohaimin, Mahizun; Ismail, Halim; Ismail, Azizi; Che Noh, Aderi (Nilai Polytechnic Negeri Sembilan, 2021)
Textbooks are one of the main teaching resources in Teaching and Facilitation (PdPC) sessions. The change of the PdPC education system face to face to Teaching and Learning at Home (PdPR) is changing the way of learning in Malaysia whether at the primary, secondary and institutions of higher learning. The use of printed textbooks during PdPC has changed to the use of digital textbooks during PdPR. The purpose of this study is to identify the challenges of using digital textbooks of Islamic Education Primary School Standard Curriculum (KSSR) during PdPR and propose solutions to overcome these challenges. This study is qualitative in nature by obtaining data through interviews and document analysis. The study found that the challenges in conducting PdPR exist in terms of teachers, students and materials. Several solutions have been proposed to overcome these challenges. The conclusion is that textbooks still remain the main resource in PdPC sessions even when conducted online. This study has implications for Islamic Education teachers to apply digital textbooks during PdPR.